2010
DOI: 10.1002/jae.1165
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic treatment effect analysis of TV effects on child cognitive development

Abstract: We investigate whether TV watching at ages 6-7 and 8-9 affects cognitive development measured by math and reading scores at ages 8-9 using a rich childhood longitudinal sample from NLSY79. Dynamic panel data models are estimated to handle the unobserved child-specific factor, endogeneity of TV watching, and dynamic nature of the causal relation. A special emphasis is put on the last aspect where TV watching affects cognitive development which in turn affects the future TV watching. When this feedback occurs, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…Reading should improve children's reading recognition skills. Computer use may have positive affect both types of cognitive skills and television may improve reading skills (Fiorini 2010; Malamud and Pop-Eleches, 2011; Beuermann et al, 2013; Gentzkow and Shapiro, 2008; Huang and Lee, 2010). Some active leisure activities, for example, team sports and educational games, may also positively affect cognitive skills.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Reading should improve children's reading recognition skills. Computer use may have positive affect both types of cognitive skills and television may improve reading skills (Fiorini 2010; Malamud and Pop-Eleches, 2011; Beuermann et al, 2013; Gentzkow and Shapiro, 2008; Huang and Lee, 2010). Some active leisure activities, for example, team sports and educational games, may also positively affect cognitive skills.…”
Section: Datamentioning
confidence: 99%
“…According to the findings of Fiorini (2010), Malamud and Pop-Eleches (2011), and Beuermann et al (2013),computer use fosters verbal and non-verbal intelligence. Gentzkow and Shapiro (2008) and Huang and Lee (2010) conclude that moderate television watching improves children's reading ability.…”
Section: Introductionmentioning
confidence: 99%
“…Because 1 À g h θ 1 > 1, the sign of g à y depends on the sign of g h θ 2 + g y that consists of the direct effect g y of y 2 on y 1 and the 'indirect effect' g h θ 2 < 0 through the improved health; see Huang and Lee (2010) and Lee and Huang (2012) for this type of decomposition of a total effect into the direct and indirect effects. Because 1 À g h θ 1 > 1, the sign of g à y depends on the sign of g h θ 2 + g y that consists of the direct effect g y of y 2 on y 1 and the 'indirect effect' g h θ 2 < 0 through the improved health; see Huang and Lee (2010) and Lee and Huang (2012) for this type of decomposition of a total effect into the direct and indirect effects.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Huang and Lee (2010) also showed that the G ‐algorithm reduces to the above total effect under conditions (a) and (b). The linear model assumption is critical for this, as well as for the decomposition of the total effect into the direct and indirect effects.…”
Section: Various Approaches To Dynamic Treatment Effectsmentioning
confidence: 99%
“…Huang and Lee (2010) showed that this holds if for which the above conditions (a) and (b) are sufficient. This kind of ‘selection‐on‐observables’ condition is pervasive in the literature, and it is also called ‘conditional independence’ or ‘ignorability’.…”
Section: Various Approaches To Dynamic Treatment Effectsmentioning
confidence: 99%